2011
DOI: 10.1093/jnci/djr207
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Misclassified Underlying Cause of Death on Survival Estimates of Colon and Rectal Cancer

Abstract: Inaccurate coding of patients' Underlying Cause of Death (UCOD) has constrained cause-specific survival estimates for colon and rectal cancers. Using California data from the Accuracy of Cancer Mortality study, we compared the cancer site data from the California Cancer Registry (CCR) with UCODs reported on death certificates and reclassified the UCODs based on cancer registry data when they disagreed. We then calculated 1-, 3-, 5-, and 10-year cause-specific survival for colon and rectal cancers separately, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
50
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 21 publications
3
50
0
1
Order By: Relevance
“…In 1981, Percy et al reported that misclassification led to over reporting of colon cancer deaths and underreporting of rectal cancer deaths [27]. More recently, in the US, Yin et al reported inaccurate coding of underlying cause of death, with the vast majority of misclassifications being colon cancers incorrectly classified as rectal cancers [28]. Further investigation is warranted to explore the extent and nature of misclassification on death certificates in European countries in recent years, perhaps comparing countries with rising and static rectal cancer mortality rates.…”
Section: Discussionmentioning
confidence: 99%
“…In 1981, Percy et al reported that misclassification led to over reporting of colon cancer deaths and underreporting of rectal cancer deaths [27]. More recently, in the US, Yin et al reported inaccurate coding of underlying cause of death, with the vast majority of misclassifications being colon cancers incorrectly classified as rectal cancers [28]. Further investigation is warranted to explore the extent and nature of misclassification on death certificates in European countries in recent years, perhaps comparing countries with rising and static rectal cancer mortality rates.…”
Section: Discussionmentioning
confidence: 99%
“…Misclassification has been reported for CRC as the underlying cause of death, although most of inaccuracies were due to death certificates assigning colon as the cause of death for rectal cancer patients, due to the interchangeable use of the terms colon and colorectal. 14 In addition, screening quality may differ between whites and Hispanics, which could attenuate the preventive effect of polyp removal. Despite these limitations, the size and diversity of the California population and the quality of CCR data are important factors in bringing to light the disparities uncovered in this study.…”
Section: Rates Among Hispanics Did Not Decline Until 2008 (Table 2)mentioning
confidence: 99%
“…12 Second, measuring cancer-specific survival is inherently difficult as data from death certificates is often inaccurate and may not reflect cancer-associated mortality in patients who die from complications and the sequelae of cancer. 13,14 …”
Section: Introductionmentioning
confidence: 99%